Reducing Losses of Milk Production at KPBS Pengalengan – West Java (Focused study on Social and Economical Analysis) - Dodik Suprapto (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2018)
This research examines the profile of dairy farms and the strategic steps of KPBS Pengalengan as a milk cooperative that connecting between they members and milk industries to reduce losses in milk production, improve quality of fresh milk and influence welfare of the members. The objective research focused on animal health, milking hygiene, nutrition (feed and water), and socio-economic management. The result showed that KPBS Pengalengan policy to improve the quality of fresh milk with determine the price of milk based on the quality of fat, total solid and TPC, also built Milk Collecting Point (MCP) at the central of farm. This strategy are effective for changing the mindset of farmers, reducing losses of milk production and increasing the income members.